2020
DOI: 10.3133/ofr20201060
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risks posed by SARS-CoV-2 in and via North American bats — Decision framing and rapid risk assessment

Abstract: A guidance committee, composed of representatives from several State and Federal wildlife agencies, was instrumental in helping us frame the decision context for this risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(91 citation statements)
references
References 4 publications
2
89
0
Order By: Relevance
“…Cross-species virus transmission events are relatively rare, requiring an infectious reservoir host to be in contact with a recipient host when conditions concurrently favor susceptibility and onward transmission [12,113,114]. The currently unknown, but possible and potentially high-consequence, risk of SARS-CoV-2 transmission and establishment in North American bats (or other free-ranging mammals) warrants precaution [116,140]. Strategically managing interactions between people and potentially susceptible or at risk species can decrease the probability of cross-species virus spillover [113].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-species virus transmission events are relatively rare, requiring an infectious reservoir host to be in contact with a recipient host when conditions concurrently favor susceptibility and onward transmission [12,113,114]. The currently unknown, but possible and potentially high-consequence, risk of SARS-CoV-2 transmission and establishment in North American bats (or other free-ranging mammals) warrants precaution [116,140]. Strategically managing interactions between people and potentially susceptible or at risk species can decrease the probability of cross-species virus spillover [113].…”
Section: Resultsmentioning
confidence: 99%
“…For example, PPE, including respiratory protection, is a standard practice adopted by many bat virus researchers but by few others studying and regularly handling bats [ 134 , 139 ]. The urgent research priority of a rapid, quantitative risk assessment and analysis of various mitigation options is currently underway [ 137 , 140 ]. One key question is whether the proper use of optimal PPE, including bidirectional N95 or equivalent masks, along with effective risk communication and adherence to other basic biosafety practices [ 134 , 141 , 142 ] during field work, can significantly reduce the transmission risk of SARS-CoV-2 from humans to bats.…”
Section: Need For An Interdisciplinary Responsementioning
confidence: 99%
“…In an earlier risk assessment focused on spring and summer fieldwork conditions, Runge et al (2020) had to rely almost entirely on expert judgment for parameters in their risk model. Since that time, a substantial amount of empirical data have accrued, and the risk assessment described here was able to incorporate empirical estimates for over half of the parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In April 2020, Runge et al (2020) conducted an assessment of the risk of SARS‐CoV‐2 infection in bats via contact with humans conducting research, survey, monitoring, wildlife control, and rehabilitation work in summer fieldwork settings. They found that the risk to bats was low if personal protective equipment (PPE) was properly used, but there was significant uncertainty about whether infection could result in spread within bat populations.…”
Section: Introductionmentioning
confidence: 99%
“…3) of these viruses from humans into novel bat or other animal hosts that have no evolutionary association with the circulating strains. Bat organisations internationally have responded to this threat by advocating, at a minimum, for increased biosecurity protocols when handling bats for research or rehabilitation (IUCN Bat Specialist Group 2020; Olival et al 2020;Runge et al 2020). In some cases, this has extended to blanket bans on handling wild bats.…”
Section: Potential Establishment Of Novel Coronaviruses In Australianmentioning
confidence: 99%